2015
DOI: 10.1007/s00894-015-2747-5
|View full text |Cite
|
Sign up to set email alerts
|

π-Hole interaction: a theoretical insight into the mechanism of SO2 captured by [Et2NEMim][Tetz] ionic liquids

Abstract: The mechanism of SO2 capture by 1-(2-diethylaminoethyl)-3-methylimidazolium tetrazolate ([Et2NEMim][Tetz]) was investigated using B3LYP hybrid density functional methods at 6-31 + G(d,p) level. In order to find the origin of the high capacity of the subjected ionic liquids (IL) for SO2 capture, the 1: n (n = 1-5) complexes formed between [Et2NEMim][Tetz] and 1-5 SO2 molecules were optimized. Two interaction modes (π-hole interaction and hydrogen bond) were found in each 1: n (n = 1-5) complex; the second order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[Tetraz]-based ILs, which have four electronegative N atoms, are typical examples of multisite ILs. 88 Chen et al used [P 66614 ][Tetraz] to capture SO 2 , and the absorption pathway is shown in Figure 8a. 89 According to this mechanism, 1 mol [P 66614 ][Tetz] should absorb 4 mol SO 2 molecules, but the experimental results showed that only 3.72 mol of SO 2 was absorbed, which is lower than the theoretical solubility.…”
Section: Evaluation Of Phase Change Absorbentsmentioning
confidence: 99%
“…[Tetraz]-based ILs, which have four electronegative N atoms, are typical examples of multisite ILs. 88 Chen et al used [P 66614 ][Tetraz] to capture SO 2 , and the absorption pathway is shown in Figure 8a. 89 According to this mechanism, 1 mol [P 66614 ][Tetz] should absorb 4 mol SO 2 molecules, but the experimental results showed that only 3.72 mol of SO 2 was absorbed, which is lower than the theoretical solubility.…”
Section: Evaluation Of Phase Change Absorbentsmentioning
confidence: 99%
“…53 As listed in Table S3 The main reason for these high capacities is that both the cation and the anion could capture SO 2 chemically. 58,59 Interestingly, [Et 2 NEmim][PF 6 ] is hydrophobic, indicating that the SO 2 absorption mechanism is different in the presence or absence of water, as shown in Scheme 10. 2,51 In the presence of water, SO 2 can dissolve in water to generate H 2 SO 3 , which is acidic and ionizes to H + and HSO 3 − .…”
Section: [Glycerol] [Tmg][pbe] [Tmg][sub] [Tmg][suc] and [Tmg]mentioning
confidence: 99%
“…What is more, [Et 2 NEmim]­[PF 6 ] can absorb 0.94 mol of SO 2 per mol of IL (30 °C, 3% SO 2 ), and [Et 2 NEMim]­[Tetz] can capture 0.47 g of SO 2 /g of IL at 0.1 bar SO 2 partial pressure. The main reason for these high capacities is that both the cation and the anion could capture SO 2 chemically. , Interestingly, [Et 2 NEmim]­[PF 6 ] is hydrophobic, indicating that the SO 2 absorption mechanism is different in the presence or absence of water, as shown in Scheme . , In the presence of water, SO 2 can dissolve in water to generate H 2 SO 3 , which is acidic and ionizes to H + and HSO 3 – . Subsequently, H + can react with the basic moieties of ILs, such as amine and anions, to form [ILH] + HSO 3 – (Scheme ).…”
Section: Ionic Liquid For So2 Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al presented a series of dual-functionalized ILs for SO 2 absorption through chemical absorption combined with physical absorption. Subsequently, other ILs with kinds of functional groups have been used for SO 2 capture with high efficiency, including azolate, tertiary amine, cyano, carbonyl, carboxylate, , phenolate, , and ether. It is proved that the electron-negative N and O atoms are main active sites in these ILs. Compared with sites in the cations, it is known that sites in the anions are more active and can be a key contributor to ILs for gas capture. , When a strong active site and a weak active site are both in one anion, the strong site will preferentially react with SO 2 .…”
Section: Introductionmentioning
confidence: 99%